To a problem of introduction of information and communication technologies in process of learning in Computer Science at secondary schools of Ukraine (Pedagogy of Higher and Secondary Education, 2014)
Donchenko I. A. To a problem of introduction of information and communication technologies in process of learning in Computer Science at secondary schools of Ukraine.Stages of implementation of ICT in the learning process of computer science and features of forms and methods of using ICT in educational process at various stages of the introduction of modern technologies in secondary schools in Ukraine were determined in the article. Preconditions of the introduction of information technology into the learning process of computer science in secondary schools were identified. Questions of contents of the concept «information and communication technology» at different stages of their implementation in the educational process in schools in Ukraine were revealed.
Keywords: innovation; factor; communication technology; information technology; the learning process; information; forms of training; periodization